THE PROSPECTS OF CORPORATE FINANCIAL AND ECONOMIC ACTIVITY AND THEIR EFFECTIVE MANAGEMENT - Mamadullayev Isomiddin Xasan o‘g‘li (Scholar Express Journals, 2023)
This article describes the features of corporations' recovery of financial and economic activity and the factors of recovery of financial and economic activity. Prospects for effective management of financial and economic activities of corporations are also presented.
Keywords: corporation; corporate management; financial and economic activity; investment